ERECTILE DYSFUNCTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND ITS CORRELATION WITH SERUM TESTOSTERONE LEVELS - Haider, Iqbal; Malik, Suleman Elahi; Munib, Nayab; Hassan , Subtain; Khan, Wahab; Khan, Raheel Ahmad (Journal of Postgraduate Medical Institute, 2024)
Objective: To determine erectile dysfunction in patients with Type 2 Diabetes Mellitus (DM-II) and its correlation with serum testosterone levels. Methodology: Patients with type 2 diabetes participated in this prospective cross-sectional study at Department of Medicine, Khyber Teaching Hospital Peshawar from October 2022 to April 2023. After approval from institutional ethical review board, strict inclusion/exclusion criteria were followed to minimize the confounders. The sample size was calculated by OpenEpi.com, keeping the prevalence of erectile dysfunction in Pakistani diabetics at 97.8% with 5% as the error margin and a 95% confidence level. The data were recorded on well-designed questionnaire and Lynn criteria validated these items having a threshold of 0.80 by six subject experts. An SPSS version 22.0 was used to analyze various variables statistically and a p-value of 0.05 or lower was regarded as significant. Results: Amongst one hundred and fifty type- 2 diabetic male patients, 87 (58%) of the study population had ED. Fifty-three (35.3 %) had hypertension (HTN), 18 (12%) had dyslipidemia, and 63 (42%) had diabetic complications as co-existent co-morbidities. There were more patients with Low testosterone and ED 58.6% (n=51) than those with normal testosterone and ED 43.1% (n=36). Among T2DM patients with ED (n=87), 75.8% had poor glycemic control (HbA1c >8%) and among hypertensive patients (n=53), 81.1% had ED. Conclusion: Erectile dysfunction is common in poorly controlled diabetics and diabetes of long duration. In our study, there is no substantial relationship between testosterone levels and ED.